Comparison of the resistance of intrarradicular pin of glass fiber with experimental pin connected by CAD/CAM technology (Research, Society and Development, 2020)
Objective: The aim of the present study was to compare the fracture strength of endodontically restored teeth with glass-fiber pin and experimental pin of computer-aided design / computer-aided manufacturing (CAD / CAM). Methodology: A total of 20 bovine incisors with sectioned crowns and roots were prepared with 15mm length were randomly divided into two groups (n = 10): G1 - pin fiber glass (control) and G2 - pin machined (experimental). In both groups, the samples had their root canals treated endodontically. The roots were included in acrylic resin, the pins cemented with dual resin cement and subsequently subjected to the compression fracture strength test at a speed of 0.05 mm / min under a 45 ° angle in a universal test machine until the fracture. The values of fracture resistance were submitted to Student's t-test with the SPSS program with a significance level of 5%. Results: According to the tests, the results required strength at fracture was lower in the pre-fabricated custom (48.2kgf) fiber pin group than the group of pins milled by the CAD / CAM system (56.9kgf), however no there was a statistical difference between them (p = 0.26). With a mean SD ± 14.6 for the first and ± 19.0 for the second group. Conclusion: Fiber pins developed by CAD / CAM technology may appear as a viable alternative for intraradicular restorations of endodontically treated elements, since there was no statistical difference in fracture resistance with pre-fabricated pins.